Valorización energética de harina de palmiste utilizado en la alimentación de pollos de engorde. - Lalama Santamaría, Diana Carolina (2022)
The current research was made in the Huachi Grande Parish, Manzana de Oro sector, belonging to the Ambato city, Tungurahua province, it had with 17 experimental units, what were made up by discarded breeding males, two years old. In the poultry industry, it is called broiler chicken, the bird that is raised especially for meat, due to the high demand in the market, it must present high growth rates, and feed conversion, further, to feasibility, productivity and meat quality. The current research general aim is to determine the palm kernel flour energy value extracted by different methods, through into vivo digestibility tests. It was used metabolic exclusion cages. Solvent extracted palm kernel meal recorded higher digestibility coefficients for Crude Fiber 84.89%, Ethereal Extract 82.80%, Organic Matter 75.95%, Nitrogen-Free Extract 66.81%, and Calcium 79.14%. While the palm kernel flour extracted by Mechanical Pressure presents an increase in the digestibility coefficients for Dry Matter 72.00%, Gross Protein 80.52%; furthermore, the highest value True Metabolizable Energy by showing with 545.67 Kcal/kgMS, showing, which the palm kernel flour combined with the two methods (solvent and mechanical pressure) presents a VME (518.45 Kcal/kgMS) least content.